PRAKTIK KOMUNIKASI BISNIS PT ASTRA INTERNATIONAL TBK – TOYOTA AUTO2000 SALES OPERATION, TOYOTA SBY WARU - Muzayanah, Lilik (Seminar Nasional Manajemen, 2025)
The internship activity in the Business Communication Practice course was carried out at PT Astra International Tbk – Auto2000 Waru as part of the Merdeka Belajar Kampus Merdeka (MBKM) program. This activity was based on the importance of business communication in facing business competition in the globalization era, where effective communication strategies play a crucial role in maintaining company existence through promotion, marketing, and customer relationship management. The main objective of this internship was to enhance students’ skills in creating a company profile, preparing meeting minutes, conducting product promotion presentations, and designing digital-based promotional media. The method used involved direct practice in the company through observation, active participation, and digital content production, which was published on the company’s social media platforms such as TikTok and YouTube. The results showed that students successfully produced a company profile in video format, systematically prepared meeting minutes, delivered product promotion presentations, and created effective promotional media designs. This activity provided significant benefits for students, the university, and the company, and proved that mastering business communication can support organizational goals while providing students with applicable practical experience.